Synthesis of (±)‐Tetrapetalone A‐Me Aglycon1. Issue 35 (7th July 2014) - Carlsen, Peter N.; Mann, Tyler J.; Hoveyda, Amir H.; Frontier, Alison J.
Abstract The first synthesis of (±)‐tetrapetalone A‐Me aglycon is described. Key bond‐forming reactions include Nazarov cyclization, a ring‐closing metathesis promoted with complete diastereoselectivity by a chiral molybdenum‐based complex, tandem conjugate reduction/intramolecular aldol cyclization, and oxidative dearomatization.